2018
DOI: 10.1007/s00394-018-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of sugar sweetened beverages consumption with non-alcoholic fatty liver disease: a systematic review and meta-analysis

Abstract: This meta-analysis supports a positive significant association between higher consumption of SSB and NAFLD in both men and women. These findings strengthen the evidence that intake of SSBs should be limited to reduce fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 59 publications
6
45
0
3
Order By: Relevance
“…The main risk factors for primary NAFL and NAFLD ( Table 1 ) are overweight/obesity, insulin resistance/type 2 diabetes, hypertriglyceridaemia and the related dietary-behavioural triggers, primarily the intake of beverages sweetened with fructose. By itself, in different observational studies [ 5 ], only consumption of sugared soft drinks (mainly with fructose) increases the risk of developing NAFLD of around 55% [ 6 ]. Among the emerging risk factors there are also the smoking habit and the Obstructive Sleep Apnoea Syndrome (OSAS), but also insomnia and excessive daytime sleepiness unrelated to nocturnal sleep apnoea [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factors for primary NAFL and NAFLD ( Table 1 ) are overweight/obesity, insulin resistance/type 2 diabetes, hypertriglyceridaemia and the related dietary-behavioural triggers, primarily the intake of beverages sweetened with fructose. By itself, in different observational studies [ 5 ], only consumption of sugared soft drinks (mainly with fructose) increases the risk of developing NAFLD of around 55% [ 6 ]. Among the emerging risk factors there are also the smoking habit and the Obstructive Sleep Apnoea Syndrome (OSAS), but also insomnia and excessive daytime sleepiness unrelated to nocturnal sleep apnoea [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that high intake of eicosapentaenoic acid and docosahexaenoic acid [42], magnesium [43], and vitamin C [44] is linked to low prevalence of fatty liver diseases. In contrast, consumption of refined carbohydrates may increase hepatic de novo lipogenesis and risk of fatty liver diseases [45]. Based on this existing knowledge, our finding that there were no notable differences before and after adjustment for dietary pattern scores indicates that dietary patterns may be confounding in both positive and negative ways, rather than dietary patterns not being a confounder.…”
Section: Discussionmentioning
confidence: 54%
“…The preservation of systemic insulin responsiveness (and glucose tolerance; Supplementary Figure 2) in our model demonstrate a clear decoupling of the mechanisms responsible for steatosis and those responsible for impairments in insulin sensitivity following chronic sucrose intake and, in the case of female mice, overt obesity ( Figure 1A). In humans, sugar sweetened beverage consumption is strongly associated with NAFLD (Arenaza et al, 2019;Asgari-Taee et al, 2019;Assy et al, 2008;Cahlin et al, 1973;Chen et al, 2019;Ma et al, 2015) but not always with obesity (Te Morenga et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from observational studies and meta analyses indicate that excessive sugar intake or compromised sugar metabolism may be an initiating factor for NAFLD in humans (Arenaza et al, 2019;Asgari-Taee et al, 2019;Assy et al, 2008;Cahlin et al, 1973;Chen et al, 2019;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%